2020
DOI: 10.3390/nu12010148
|View full text |Cite
|
Sign up to set email alerts
|

Low FODMAP Diet: Evidence, Doubts, and Hopes

Abstract: Food is often considered to be a precipitating factor of irritable bowel syndrome (IBS) symptoms. In recent years, there has been a growing interest in FODMAPs (Fermentable Oligo-, Di-, Mono-saccharides, And Polyols), which can be found in many common foods. A low FODMAP diet (LFD) is increasingly suggested for IBS treatment. However, long-term, large, randomized controlled studies are still lacking, and certainties and doubts regarding LFDs have grown, often in a disorderly and confused manner. Some potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
82
0
25

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 99 publications
0
82
0
25
Order By: Relevance
“…In recent years, the LFD has gained increasing popularity among gastroenterologists and patients. Even if it cannot be considered a panacea for all patients affected with GI disturbances, there are now several studies proving its efficacy [8]. Indeed, a recent systematic review provided evidence that an LFD is effective in improving IBS symptoms [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, the LFD has gained increasing popularity among gastroenterologists and patients. Even if it cannot be considered a panacea for all patients affected with GI disturbances, there are now several studies proving its efficacy [8]. Indeed, a recent systematic review provided evidence that an LFD is effective in improving IBS symptoms [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear whether the patients are really able to precisely recognize the foods which trigger their symptoms or if they simply think they are intolerant to some foods, often depicted as dangerous by the media, relatives and friends, e.g., gluten and/or lactose. A relatively new approach to IBS therapy is the restriction of short-chain fermentable oligosaccharides, disaccharides, monosaccharides and polyols (FODMAP), the so-called low-FODMAP diet (LFD) [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not known whether the impact of the low FODMAP diet on the gut microbiota is long-term, as longitudinal follow-up is only seldomly included in current studies. In addition, most of the studies only report microbiota changes at the end of a restrictive period (4-8 weeks) but do not consider the suggested reintroduction phase, in which fermentable carbohydrate restriction becomes less stringent [78]. With the exception of Harvie et al [25], who found persistent symptom improvement in IBS patients with the reintroduction of FODMAPs, yet did not observe any microbial changes upon the FODMAP diet or 3 months thereafter (possibly due to a loss of samples after a technical issue), the long-term impact of a low FODMAP diet is currently unassessed.…”
Section: Discussionmentioning
confidence: 99%